ANALISIS TINGKAT PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM ALOKASI DANA DESA DI KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG - Muh Arifai; Mattarima Mattarima (LP2M IBK Nitro, 2022)
This study uses a quantitative approach. The sample in this study found 45 people from three villages, namely Patobong Village, Samaenre Village and Mattiro Tasi Village. Data was collected by using the methods of observation, questionnaires and interviews. The results of the research conducted showed that the level of participation in Mattiro Sompe Subdistrict, Pinrang Regency was good, this was the maximum and high coordination between the government and the community based on several good aspects of the community, it was proven that the number of people after the recapitulation showed a high level with the acquisition of 51.1 % is in the agree category. At the implementation stage 40.4% agreed. Furthermore, regarding utilization, with 44.4% gains, they agreed. Then at the stage of assessment of the results of the development shows the percentage results of 43.6% agree. Thus, it is known that the level of community participation in the Mattiro Sompe sub-district is quite proactive and high so that the village community enjoys the results that have been achieved so far